Presentation and representation in Trilce: Home path through Avant-Gardes - Smith Soto, Alan (2022)
Written and revised between 1918 and 1922, Trilce shares and devours the fundamental avant-garde trope, which eschews representation through the sign’s own opacity, now protagonist of its own presence, freed from the ancillary duty of mimesis. Against the critical and creative discourses of that time —in the literary, plastic and musical arts—, this study considers Vallejo’s own resolute direction.